Limitation of Na-H codoping in achieving device-quality p-type ZnO. (October 2017) - Li, Junqiang; Liu, Yaoping; Mei, Zengxia; Vines, Lasse; Kuznetsov, Andrej; Du, Xiaolong
Abstract: Na-H in-situ codoping in single crystalline ZnO films was carried out by plasma assisted molecular beam epitaxy. It is found that Na-H codoping dramatically enhances the formation of substitutional Na (NaZn ) in ZnO lattice due to the unchanged Fermi level. The annealing temperature needed to kick out H, however, is very high, which would concurrently result in a notable decrease of Na concentration to its solution limit in ZnO, namely, in the range of 10 17  cm −3 . Our results suggest that Na-H codoping method has a limited effect on enhancing the p-type conductivity of ZnO.